Experimental and Numerical Study of Pressure Intensity in Detachable Joints of D Series Pumps - Андрій Руденко; Владислав Зубко; В’ячеслав Хворост; Андрій Лисенко (Mechanics and Advanced Technologies)
The object of study is a single-stage double-suction axially split volute casing centrifugal pump.